Cantharis by photosynthetic bacteria biotransformation: Reduced toxicity and improved antitumor efficacy. (20th June 2016) - Yu, Man; Zhao, Yue
Abstract: Ethnopharmacological relevance: The blister beetle, also known as Mylabris cichorii, is not only widely used in clinical applications in Chinese anticancer medicine, but is also one of the main ingredients in a variety of traditional Chinese medicinal preparations with anticancer activity. However, the strong toxicity exhibited by this beetle species limits its clinical applicability, with the photosynthetic bacteria featuring a strong biological conversion function. Therefore, in this study we explore the use of photosynthetic bacteria for bioconversion of the blister beetle in order to reduce the toxicity and in effort to enhance the overall antitumor effect. Methods and results: In the first set of experiments, we utilized an orthogonal experimental design to optimize the culture medium of photosynthetic bacteria. Concurrently, the growth curve of photosynthetic bacteria was used to determine the inoculation amount of the photosynthetic bacteria and the safe concentration of cantharis. Through antitumor activity experiments conducted in vitro we found that the inhibition rate increased through cantharis by PSB biotransformation of HepG2, A549 and BEL-7406 cells. Furthermore, through acute toxicity tests in mice it was found that the blister beetle water extraction liquid exhibits a LD50 value of 1383 mg/kg, while the blister beetle transformation liquid exhibits a LD50 value of 206 mg/kg. The LD50 value of the blister beetle water extract was found to be 6.7 times higher than the transformation liquid, thus demonstrating that the toxicity of cantharis by PSB biotransformation may be decreased. More strikingly, decreased toxicity was observed in the mouse liver and in pathological sections of the kidneys after transformation. Conclusions: In this paper we demonstrate for the first time that PSB bioconversion of the blister beetle is able to reduce the toxicity of a common method used in anticancer treatments as part of the principles in traditional Chinese medicine and may therefore improve antitumor activity in vitro. Graphical abstract: